1997
DOI: 10.1002/(sici)1097-0142(19970701)80:1<75::aid-cncr10>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

The results of intraoperative consultations in 181 ductal carcinomas in situ of the breast

Abstract: respectively. Sampling error was the main reason for the low detection rate, and technical inadequacy was a major factor contributing to interpretive problems. In multivariate regression analysis, FS accuracy was significantly associated with the clinical presentation of a palpable mass (odds ratio [OR] Å 4.16, 95% confidence interval [CI]: 2.04-8.45), the macroscopic finding of a mass (OR Å 3.03, 95% CI: 1.45-6.67), and necrosis (OR Å 3.13, 95% CI: 1.4-6.67). CONCLUSIONS.The authors concluded that the accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The following factors were found to contribute to the pitfalls and misinterpretations: 1) misinterpretation (insufficient expertise), 2) poor quality of the FS (artifacts making diagnosis difficult), 3) sampling errors during sectioning, 4) ignorance of macroscopic features, 5) lesions difficult to interpret (hard cases), 6) ductal carcinoma in situ (DCIS) as the only lesion in the specimen, and 7) sections not deep enough (focal nature of the lesion). Several of the factors were often present together ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The following factors were found to contribute to the pitfalls and misinterpretations: 1) misinterpretation (insufficient expertise), 2) poor quality of the FS (artifacts making diagnosis difficult), 3) sampling errors during sectioning, 4) ignorance of macroscopic features, 5) lesions difficult to interpret (hard cases), 6) ductal carcinoma in situ (DCIS) as the only lesion in the specimen, and 7) sections not deep enough (focal nature of the lesion). Several of the factors were often present together ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, FSA requires increased surgical time and has reduced accuracy compared with paraffinembedded histology (15)(16)(17)(18)(19). FSA studies have reported sensitivities between 65% and 91% and specificities between 85% and 100% (16,17,(20)(21)(22)(23), and false-negative rates as high as 36% for small (<1 cm) or nonpalpable lesions, such as DCIS (24). FSA is particularly difficult in fatty breast specimens, and freezing artifacts make subsequent diagnosis on paraffin-embedded sections more difficult (25,26).…”
mentioning
confidence: 99%
“…Certainly, the accuracy of diagnosing DCIS by frozen section has been questioned in several series. 160,161 Even for small and low-grade cancers, the source of many equivocal needle biopsy results, frozen section diagnosis may not be completely reliable. Even when the diagnosis of cancer by needle biopsy is secure, definitive excision and full assessment of the size and histopathology of nonpalpable T1a and selected T1b cancers by paraffin section, as previously discussed, best enables an appropriate decision on whether additional surgery, such as sentinel lymphadenectomy, should be performed.…”
Section: Should Frozen Section Diagnoses Be Obtained For Nonpalpable mentioning
confidence: 99%